The Best Village Apparatus Decision Support System in Beji Village with the Competency Gap Method - Musyafa, Muhamad Fahmi; Tahyudin, Imam (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
Human Resources (HR) owned by employees is an important element in a company. Human resource management is a determining aspect of the work success of a company. If employee performance can be managed properly, it is expected that the company can run all its business processes properly. The purpose of this study was to determine the best village apparatus using the Gap Competency method. This method can be used to determine the best employees from predetermined criteria. The criteria assessed are Professionalism, Discipline, and the ability to work together. Based on the results of the analysis of the 10 performances of the Beji village apparatus, the first rank was Muslikh with a value of 3.76, the second Romini with a value of 3.524, and the third Samingun with a value of 3.504.